Mexican native trouts: a review of their history and current systematic and conservation status - Hendrickson, Dean A.; Pérez, Héctor Espinosa; Findley, Lloyd T.; Forbes, William; Tomelleri, Joseph R.; Mayden, Richard L.; Nielsen, Jennifer L.; Jensen, Buddy; Campos, Gorgonio Ruiz; Romero, Alejandro Varela; van der Heiden, Albert; Camarena, Faustino; et al. (Reviews in fish biology and fisheries, 2002)
While biologists have been aware of theexistence of native Mexican trouts for over acentury, they have received little study. Thefew early studies that did much more thanmention their existence began in the 1930s andcontinued into the early 1960s, focusingprimarily on distributional surveys andtaxonomic analyses. Starting in the 1980s theBaja California rainbow trout became thesubject of more detailed studies, but verylittle remains known of mainland trouts of theSierra Madre Occidental. We review earlierstudies and report on our own collections andobservations made between 1975 and 2000. Wepresent newly discovered historical evidencethat leads us to conclude that a "lost"cutthroat trout, a lineage not previously knownfrom Mexico, was collected more than a centuryago from headwaters of the Río Conchos (amajor tributary of the Rio Grande (= RíoBravo)), a basin not previously considered toharbor a native trout. We review the lastcentury of regional natural resource managementand discuss our own observations of trouthabitats. Impacts of logging, road building andovergrazing are widespread and expanding. Manystreams suffer from heavy erosion, siltationand contamination, and though long-termhydrologic data are generally not available,there is evidence of decreased discharge inmany streams. These problems appear related toregion-wide land management practices as wellas recent regional drought. Trout cultureoperations using exotic rainbow trout haverapidly proliferated throughout the region,threatening genetic introgression and/orcompetition with native forms and predation onthem. Knowledge of distribution, abundance,relationships and taxonomy, not to mentionecology and population biology, of nativetrouts of the Sierra Madre Occidental remainsinadequate. Vast areas of most mainlanddrainages are still unexplored by fishcollectors, and even rudimentary informationregarding basic biology, ecology and populationstructure of stocks remains lacking.Concentrated exploration, research andmanagement of this long overlooked andundervalued resource are all urgently needed.The history of natural resources exploitationthat placed so many native trouts of thewestern United States on threatened andendangered species lists is repeating itself inthe Sierra Madre Occidental. Without concertedaction and development of region-widesocio-economic solutions for current, largelynon-sustainable resource management practices,native Mexican trout gene pools will soon be ingrave danger of extinction.[PUBLICATION ABSTRACT]